Cord Blood CD8+ T Cells Have a Natural Propensity to Express IL-4 in a Fatty Acid Metabolism and Caspase Activation-Dependent Manner - Zhang, Yuxia; Maksimovic, Jovana; Huang, Bing; De Souza, David Peter; Naselli, Gaetano; Chen, Huan; Zhang, Li; Weng, Kai; Liang, Hanquan; Xu, Yanhui; Wentworth, John M.; Huntington, Nicholas D.; et al. (Frontiers in Immunology, 2018)
How T cells differentiate in the neonate may critically determine the ability of the infant to cope with infections, respond to vaccines and avert allergies. Previously, we found that naïve cord blood CD4+ T cells differentiated towards an IL-4-expressing phenotype when activated in the presence of TGF-b and monocyte-derived inflammatory cytokines, the latter are more highly secreted by infants who developed food allergy. Here we show that in the absence of IL-2 or IL-12, naïve cord blood CD8+ T cells have a natural propensity to differentiate into IL-4-producing non-classic TC2 cells when they are activated alone, or in the presence of TGF-b and/or inflammatory cytokines. Mechanistically, non-classic TC2 development is associated with decreased expression of IL-2 receptor alpha (CD25) and glycolysis, and increased fatty acid metabolism and caspase-dependent cell death. Consequently, the short chain fatty acid, sodium propionate (NaPo), enhanced IL-4 expression, but exogenous IL-2 or pan-caspase inhibition prevented IL-4 expression. In children with endoscopically and histologically confirmed non-inflammatory bowel disease (IBD) and noninfectious pediatric idiopathic colitis (PIC), the presence of TGF-b, NaPo and IL-1a or TNF-a promoted TC2 differentiation in vitro. In vivo, colonic mucosa of children with colitis had significantly increased expression of IL-4 in CD8+ T cells compared to controls. In addition, activated caspase-3 and IL-4 were co-expressed in CD8+ T cells in the colonic mucosa of children with colitis. Thus, in the context of colonic inflammation and limited IL-2 signaling, CD8+ T cells differentiate into non-classic TC2 that may contribute to the pathology of inflammatory/allergic diseases in children.